Understanding the complex role of exosomes in intestinal ischemia-reperfusion injury: from pathogenesis to protection - Ye, Qin; Yu, Zi-Hang; Nie, Liang; Wang, Fei-Xiang; Mu, Guo; Lu, Bin (Frontiers in Pharmacology, 2025)
Extracellular vesicles, which are predominantly classified into ectosomes and exosomes, are released by all cells under both physiological conditions and in response to acquired pathological states. Exosomes demonstrate multifaceted functions: they regulate cellular homeostasis through the elimination of redundant or detrimental intracellular components, function as mediators in intercellular signaling pathways, and serve as potential vectors for both diagnostic and therapeutic applications. Intestinal ischemia-reperfusion injury (IRI), a prevalent form of tissue and organ injury in surgical settings, has been extensively investigated. Emerging evidence indicates a crucial relationship between exosomes and intestinal IRI, specifically regarding how exosomes derived from either intestinal tissue or distant organs can modulate the pathophysiological progression of intestinal IRI. This review systematically evaluates the mechanistic roles of exosomes in intestinal IRI and their involvement in post-intestinal IRI multiple organ dysfunction, aiming to establish a theoretical foundation for therapeutic interventions and future research directions.